To solve the equation \( 5 - 3(x + 3) = 11 - 8x \), we can outline the steps as follows:
-
Distribute: Apply the distributive property to expand the left side of the equation. \[ 5 - 3(x + 3) \rightarrow 5 - 3x - 9 \]
-
Combine like terms: Simplify the left side by combining the constants. \[ 5 - 9 = -4 \quad \Rightarrow \quad -3x - 4 \] This gives us: \[ -3x - 4 = 11 - 8x \]
-
Rearrange terms: Move all terms involving \( x \) to one side and constants to the other side. Add \( 8x \) to both sides. \[ -3x + 8x - 4 = 11 \quad \Rightarrow \quad 5x - 4 = 11 \]
-
Isolate the variable: Add \( 4 \) to both sides to isolate the \( 5x \). \[ 5x = 11 + 4 \quad \Rightarrow \quad 5x = 15 \]
-
Solve for \( x \): Divide both sides by \( 5 \) to find the value of \( x \). \[ x = \frac{15}{5} \quad \Rightarrow \quad x = 3 \]
Thus, the steps taken to solve the equation \( 5 - 3(x + 3) = 11 - 8x \) result in \( x = 3 \).